Sutureless Glue Free Versus Sutured Limbal Conjunctival Autografts in Primary Pterygium Surgery - Bista, Dikshya; Byanju, Raghunandan; Gautam, Maria Alexsandronva (Nepalese Journal of Ophthalmology, 2021)
Introduction: Surgical excision is the definitive treatment for pterygium. Following excision, conjunctival autograft is usually preferred. Various methods for grafting with sutures, glue or autologous serum from the recipient bed are in use. The objective of this study was to compare surgical outcomes of sutureless glue free conjunctival autograft with sutured (vicryl 8-0) conjunctival autograft in primary pterygium excision. Materials and methods: A prospective randomized interventional study was carried out in 100 eyes with primary pterygium. They were divided into two groups for conjunctival graft adhesion; sutureless glue free (group 1; n=50 eyes) and sutured with absorbable (vicryl 8-0) suture (group 2; n=50 eyes). Time taken for surgery, complications, postoperative symptoms and overall satisfaction score were noted. The patients were followed up on day 1, day 14 and 6 weeks after surgery. Recurrence was noted till 1 year after surgery. Results: The mean age was 46.76 ± 11.97 years (group 1) and 47.24±12.76 years (group 2). Group 1 had shorter duration of surgery (p<0.001), less postoperative complaints (p<0.001) and better patient satisfaction (p<0.001) than group 2. Postoperative complications and gain in visual acuity in both the groups were not clinically significant. Recurrence was not significant in both groups until 1 year of follow up. Conclusion: Pterygium surgery with sutureless glue free conjunctival autograft had fewer postoperative complaints and better patient satisfaction than pterygium surgery with sutured conjunctival autograft. The postoperative complications, recurrence were comparable to conventional sutured technique.